CONDITIONAL CONSERVATISM SEBAGAI MEDIASI ANTARA LEVERAGE DAN INSTITUTIONAL OWNERSHIPA TERHADAP NILAI PERUSAHAAN - Dinnul Alfian Akbar (I-Finance Journal, 2019)
This research dilator behind the controversy regarding the benefits of conservative accounting numbers, intended to determine the direct effect of leverage and Institutional Ownerships on firm value, and the indirect effect of these variables through conditional conservatism as an intervening variable on company value in 2010 - 2017 in Indonesia stock exchange. The results concluded that the conditional conservatism variable cannot mediate the effect of leverage on firm value. In addition there is a direct effect between leverage and Institutional Ownerships on company value